Dampak Logical Fallacies dalam Komunikasi Bisnis terhadap Kepercayaan Konsumen pada testimoni Skincare merk X - Mintari, Nia; Asbari, Masduki; Auliya, Niki; Kimas, Taufiq (AGUSPATI RESEARCH INSTITUTA, 2025)
The decision to buy a product is strongly influenced by the level of trust that the buyer has in the item. Testimonials serve as a tool for marketers to ease consumers' fears regarding the products they want to buy. Testimonials in television commercials done through homeshopping tend to be in control. The selection of interviewees, the use of scripts, and the editing process can be considered as a way of media control over the information received by the public. This research focuses on analyzing testimonials from the point of view of the logic of the content contained. The method applied to evaluate these logical errors is qualitative content analysis. The text is divided using Toulmin's model into three parts, namely claims, grounds and warranties. In this study, logical fallacies are used as a tool to assess the logic of testimonials based on their content. The findings of this study show that there are logical fallacies present in the content of testimonials. The types of errors include false generalization, double fallacy, composition fallacy, wealth call fallacy, pity call fallacy, and compulsion call fallacy.